Composing for Japanese instruments - Miki, Minoru; Regan, Marty; Flavin, Philip (Rochester Boydell & Brewer, 2008)
The unique sounds of the biwa, shamisen, and other traditional instruments from Japan are heard more and more often in works for the concert hall and opera house. Composing for Japanese Instruments is a practical orchestration/instrumentation manual with contextual and relevant historical information for composers who wish to learn how to compose for traditional Japanese instruments. Widely regarded as the authoritative text on the subject in Japan and China, it contains hundreds of musical examples, diagrams, photographs, and fingering charts, and comes complete with two accompanying compact discs of musical examples. Its author, Minoru Miki, is a composer of international renown and is recognized in Japan as a pioneer in writing for Japanese traditional instruments. The book contains valuable appendices, one of works Miki himself has composed using Japanese traditional instruments, and one of works by other composers -- including Toru Takemitsu and Henry Cowell -- using Japanese traditional instruments.Marty Regan is assistant professor of music at Texas A&M University; Philip Flavin is a research fellow in the School of Languages, Cultures and Linguistics at Monash University, Australia.